1994
DOI: 10.5254/1.3538704
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dispersion Morphology of Silica in Rubber

Abstract: A new model of silica's aggregation in rubber, the Hexagon-linking Model, is proposed and tested in this study, using transmitting, scanning and analytical electron microscopy. When wetted in rubber, silica tends to accumulate, by way of hexagonal rings, differently from carbon black; the “wetted” states can be controlled through mixing procedures. The experimental evidence that aggregation of silica (original size of 20 nm) precedes to a final size of 63.8 nm, as compared to a theoretical value of 60 nm, supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…[10,11] The modification of silica surface with organosilanes helps to overcome this problem. In particular, bis-triethoxysilylpropyltetrasulfane (TESPT) is the most commonly used in the tyre industry since it has ethoxy groups that can bond to silica surface and sulphur atoms that can react with elastomer chains.…”
Section: Full Papermentioning
confidence: 99%
“…[10,11] The modification of silica surface with organosilanes helps to overcome this problem. In particular, bis-triethoxysilylpropyltetrasulfane (TESPT) is the most commonly used in the tyre industry since it has ethoxy groups that can bond to silica surface and sulphur atoms that can react with elastomer chains.…”
Section: Full Papermentioning
confidence: 99%
“…3 These interactions lead to the formation of secondary structures (aggregates and agglomerates) that cannot be easily broken. 4,5 As it is well known, this fact reduces not only the dispersion of the silica particles into rubber matrix, but also the interactions created between the filler particles and the rubber matrix, causing a wear reinforcing effect. 6 Several studies have shown that the surface modification of silica during processing and vulcanization processes using bifunctional coupling agents improves the silica dispersion and therefore increases the physical properties of rubber compounds filled with modified silica.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, silica was found to exert a higher reinforcement on elastomers and to improve the tyre durability and is now used in place of carbon black filler. 2 However, precipitated silica possesses a number of surface hydroxyl groups, 3,4 therefore, owing to the possibility of formation of strong intermolecular hydrogen bonds, it can aggregate 5,6 with a consequently poorer dispersion of the silica particles in the rubber. The way to avoid aggregation is to improve the compatibility between silica and rubber in order to reduce silica migration.…”
Section: Introductionmentioning
confidence: 99%